Vernonia pyramidale (D. Don) S. N. Mitra (Compositae) - A new angiospermic record for Bangladesh - Khanam, Mahbuba; Rahman, M Oliur; Yusuf, Mohammed (Bangladesh Journal of Plant Taxonomy, 2004)
No abstract available. Bangladesh J. Plant Taxon. 11(1): 99-102, 2004 (June)